Presenting a Human Rights Perspective in Administrative Law (Paradigm Offers and Administrative Court Reviewing) - Heryansyah, Despan (Fakultas Hukum Universitas Gadjah Mada, 2025)
Human Rights have not yet become the main norm and principle in the regulation and reviewing of state administrative law in the State Administrative Court. So far, state administrative law, both at the regulatory and reviewing levels, is still identified with procedures, authorities, and orders of laws and regulations. In fact, in many ways, the products of state administrative law are very intersecting with human rights, such as the eviction of agricultural land, the takeover of housing, and so on. This research shows the opposite paradigm that state administrative law is very close and closely related to human rights, so it must be the main foothold in its regulation and reviewing. This research is a type of non-doctrinal research, using secondary data as the main study. The approaches used are the statute approach and conceptual approach. The results of the study show that theoretically, departing from the contemporary meaning of the state of law, human rights and state administrative law (as an important instrument of the state of law), become a unit that is inseparable from the meaning of the state of law itself. Meanwhile, from the juridical aspect, the interpretation of Article 28I paragraph (4) and Article 5 of the Government Administration Law, has implicitly emphasized that human rights are an inseparable part of state administration. Both as the basis for government officials/organs in carrying out government functions, and as a touchstone for State Administrative Court (PTUN) judges in adjudicating administrative cases.